Retrospective analysis of CD4 count trends in South Africa - Naseem Cassim; Lindi-Marie Coetzee; Manuel P. Da Silva; Deborah K. Glencross; Wendy S. Stevens (Southern African Journal of HIV Medicine)
Background: South Africa has the largest HIV epidemic globally. Despite the scale-up of antiretroviral therapy, people living with HIV are still presenting with low CD4 counts.